The city space and the perception of environmental problems from the use of mental maps in an urban school in Rosário do Sul, RS - Severo, Melina Dornelles; Werlang, Mauro Kumpfer (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The environmental problems are stronger with the sedentarization of the man, promoting a changing in the natural landscape with the emergence of cities. Many brazilian cities have problems caused by lack of planning, pollution of air and water, water by sewage and solid waste, for irregular housing and risk areas, among many other problems that affect the life quality in cities. This study aims to evalueate, from the use of mental maps in the school, as young teenagenrs of the eigth year of the Escola Estadual de Ensino Médrio Padre Ângelo Bartelle, in the municipality of Rosário do sul, RS, perceive the urban environmental problems in the city space. To achieve this we used the concept of environmental perception from the use of mental maps. The mental maps were made by the students of the school, and in them is sought to represent some environmental problems perceived in the city space of this students. The environmental problems represented in the mental maps were those most commonly perceived in the city space. The mind maps were analysed from the phenomenological method and from the Kozel’s propose (2001). Many and various environmental problems were highlighted, however, the most frequent were related with the pollution from solid waste. It was concluded that the perception of environmental problems in the city space has a strong relation with the society’s behavior towards the consumption of products.